Whole-genome sequencing revealed a novel structural variant in COL4A4 causing autosomal dominant Alport syndrome: A case report - Clément Delage; Marine Andreani; Nihad Boukrout; Naoual Sabaouni; Michaël Perrais; Bruno Lefebvre; Christelle Cauffiez; Nicolas Pottier; Romain Larrue (Heliyon)
Next-generation sequencing has substantially transformed the genomic diagnosis of individuals affected by inherited renal disorders. Indeed, accurate and rapid diagnostic for patients with suspected genetic kidney diseases is not only important for prognosis and patient management but also for family counseling. Alport syndrome, a genetic disease primarily affecting the basement membrane, is characterized by hematuria, progressive kidney failure, hearing impairment, as well as ocular abnormalities and stems from mutations in genes encoding type IV collagen. In this study, we show the benefit of whole-genome sequencing for the molecular diagnosis of a dominant form of Alport syndrome by identifying a novel heterozygous pathogenic structural variant in a family with three affected members. This case underscores the potential of whole-genome sequencing as a frontline diagnostic approach for inherited kidney diseases and further indicates that structural variations represent an important cause of monogenic disorders.